Normal mode of dc discharge in argon, hydrogen and oxygen - Lisovskiy, V.A.; Artushenko, K.P.; Yegorenkov, V.D. (Вопросы атомной науки и техники, 2016)
This paper reports the current-voltage characteristics and the j/p²similarity parameter determination in argon, hydrogen and oxygen in the pressure range from 0.1 to 10 Torr. Experiments have been performed in the discharge tube of 56 mm inner diameter and with stainless steel electrodes. Anode diameter was 55 mm whereas the diameters of the cathodes employed were 55 and 12 mm. The j/² parameter has been shown to remain constant only at the gas pressure above 1 Torr. Its values comprise j/p²= (0.092 ±0.02) mA/(cm² ∙Torr² ) for argon, j/p²= (0.072 ±0.02) mA/(cm² ∙Torr² ) for hydrogen and j/p ² = (0.33 ±0.05) mA/(cm² ∙Torr² ) for oxygen. On lowering the pressure (below 1 Torr) the j/p²parameter grows fast and at the pressure of 0.1 Torr it may be two orders of magnitude higher than one at 1 Torr.